Cellular and molecular regulation of tumor necrosis factor-alpha production by pentoxofylline - Strieter, R.M.; Remick, D.G.; Ward, P.A.; Spengler, R.N.; Lynch, J.P.; Larrick, J.; Kunkel, S.L. (Biochemical and biophysical research communications, 1988)
Tumor necrosis factor-alpha (TNF), a mononuclear phagocyte (MO)-derived peptide, is increasingly being recognized for its pleomorphic immunologic effects. A number of investigations have demonstrated that lipopolysaccharide (LPS) can induce TNF synthesis, yet mechanisms that regulate TNF expression at the cellular and molecular levels have not been fully elucidated. In this study, we present data demonstrating pentoxifylline, a methylxanthine, is efficacious in suppressing LPS-induced MO-derived TNF at the level of both TNF mRNA accumulation and TNF supernatant bioactivity. Pentoxifylline, at a dose of 1 × 10 −5M, suppressed the production of both biologically active TNF and TNF mRNA expression by more than 50%. Furthermore, additional methylxanthines and dibutyryl cAMP have similar effects on TNF expression. These data support the mechanism for this suppressive effect is via the generation of intracellular cAMP.